ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PEGAWAI INSTALASI FARMASI DENGAN PENGGUNAAN ALAT PELINDUNG DIRI ( APD) DI RSUD KISARAN TAHUN 2021 - Sulasmi Sulasmi (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2021)
Background: PPE is a tool used to protect yourself or the body against the dangers of work accidents. The factors that influence adherence are K3 training, knowledge, behavior, age, gender. The Pharmacy Installation is a part of the hospital that manages the hospital's pharmaceutical needs, medicines, (BMHP), and medical devices. handling and controlling B3 as well as hospital injection drugs which of course have a risk of exposure to hazardous biological substances (biohazard). The purpose of this study was to analyze the factors associated with the compliance of pharmacy installation staff with the use of PPE at Kisaran Regional Hospital in 2021.Methods: This type of research used quantitative research using a cross sectional approach. The number of samples in this study were 30 people. The sample was determined by a simple technique of selecting the sample using purposive sampling. The results of the study: The data was collected using a questionnaire sheet and then processed using a statistical computer program with the chi square test with a significance level of α = 0.05 (95%). The results of the study found that the relationship of compliance with PPE use with age (p = 0.002 <α 0.05), gender (p = 0.127> α 0.05), K3 training (p = 0.004 <α 0.05), Knowledge (p = 0.018 <α 0.05) and Behavior (p = 0.011 <α 0.05). It is recommended for Kisaran Hospital to further improve the Compliance with the Use of PPE, especially for Pharmacy Installation employees.